Sensation seeking, impulsivity, and Big Five personality factors as predictors of risky behavior following concussion - Gardner, Megan M., author; Conner, Bradley T., advisor; Seger, Carol, committee member; Stephens, Jaclyn, committee member (Colorado State University. Libraries, 2020)
Sports-related concussion is a growing public health concern. With 30-50% of concussions remaining undiagnosed for a variety of reasons, it is crucial to identify risk factors and establish appropriate prevention and harm reduction strategies to prevent the risk of multiple concussions. Few studies have investigated personality factors as predictors of concussion and continued participation following an initial injury. However, research has concluded that personality likely plays a role in symptom reporting and post-injury behaviors that may put one at risk of additional injury and premature return to play. Most research on personality and health risk behaviors has focused on substance use, gambling, and criminal behavior, with little research done on personality, risky sports, and injury. The limited work in this area has concluded that the personality construct of sensation seeking is predictive of engagement in sports that have an increased risk for injury, while other constructs like impulsivity, are more predictive of injury once already participating in risky sports. The Big Five factors of personality differentially predict injury during sport such that openness to experience and extraversion predict risk-taking overall, while low levels of neuroticism and low levels of conscientiousness predict risky behavior during sport to different degrees depending on the sport studied. The current study found that sensation seeking dimensions, experience seeking and risk seeking, were positively associated with returning to play more quickly than others in the sample. Further, both of these dimensions were negatively predictive of use of protective behavioral strategies against incurring sports-related concussion. Risk seeking, attentional impulsivity, motor impulsivity, and non-planning impulsivity were found to be positively predictive of likelihood of reporting repeat sports-related concussions. Regarding the Big Five, conscientiousness was associated with taking longer to return to play, more protective behavioral strategy use, and a lower likelihood of reporting more than 1 sports-related concussion. These findings may be used in implementing individualized targeted prevention and intervention efforts for athletes. Future work should investigate the mechanisms underlying these relations, as well as include additional sports-related concussion risk factors.
Keywords: personality; injury prevention; sports-related concussion